Anatomical inferences on aerial bud protection of three Eugenia shrub species from the Cerrado. (22nd November 2022) - da Silva, G. S.; Firmino, G. V.; Ferraro, A.; Appezzato‐da‐Glória, B.
ABSTRACT: Location and degree of protection of aerial buds are important functional traits in disturbance‐ or stress‐prone environments since aerial buds ensure the development of new organs under favourable growing conditions. This study was carried out in a Brazilian Cerrado area under regeneration after long‐term Pinus cultivation, where the trees were clear‐cut in 2012 and the remaining material was burned in 2014. After the fire treatment, several species resprouted from belowground organs and their aboveground organs were directly exposed to full sunlight. We collected 15 terminal branches with fully expanded leaves from three individuals of each of three Eugenia species to investigate if those with well‐developed belowground organs invest in bark for aboveground bud protection. The samples were analysed using light and electron microscopy. In addition to terminal and axillary buds, all species presented accessory buds, and the number varied according to the node analysed. None of the aerial buds were protected by bark, but all were well protected by cataphylls and densely pubescent leaf primordia. There were also inter‐ and intra‐petiolar colleters that released a mucilaginous protein exudate. The distance between the shoot apical meristem and the outer surface was longer in the terminal bud than in axillary buds. The bud leaf primordia covering the shoot apical meristem had a thick cuticle, unicellular non‐glandular trichomes that accumulate phenolic and lipophilic compounds, and secretory cavities. Our study shows that all three Eugenia species studied here had highly protected aerial buds allocated from belowground organs. These morphological traits may improve the chances of the species' persistence in areas subjected to frost events, low relative humidity, high irradiance and harmful UV levels. Abstract : Structural and chemical attributes are associated to the protection of aerial buds, helping plants to thrive and grow in a regenerating environment.